2009
DOI: 10.1089/apc.2008.0197
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perinatal HIV Infection on Older School-Aged Children's and Adolescents' Receptive Language and Word Recognition Skills

Abstract: Perinatally HIV-infected youths are reaching adolescence in large numbers. Little is known about their cognitive functioning. This study aims to describe and compare the receptive language ability, word recognition skills, and school functioning of older school-aged children and adolescents perinatally HIV infected (HIV-positive) and perinatally HIV-exposed but uninfected (seroreverters; HIV-negative). Participants included 340 youths (206 HIV-positive, 134 HIV-negative), 9–16 years old, and their caregivers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 32 publications
7
75
1
3
Order By: Relevance
“…8,11,13 The mean IQ among HIV-infected Thai school-aged children in this study is 79 (SD 13), which is slightly lower than report from a large study among U.S. children with a mean IQ of 84 (SD 15). 8 However, in the U.S. study, the children had better immunologic status with average CD4 of approximately 690 cells.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…8,11,13 The mean IQ among HIV-infected Thai school-aged children in this study is 79 (SD 13), which is slightly lower than report from a large study among U.S. children with a mean IQ of 84 (SD 15). 8 However, in the U.S. study, the children had better immunologic status with average CD4 of approximately 690 cells.…”
Section: Discussioncontrasting
confidence: 57%
“…The study among U.S. HIV-infected and HIV-affected school-aged children focused on the receptive language ability, which is highly correlated with IQ score, found that the HIV infected group had significany lower score than HIV-affected group (mean score of 83.8 versus 87.6). 11 The recently reported data among 58 Thai HIV-infected children with median age of 7 years and median CD4 percentage of 20 showed a median (IQR) of IQ of 72 (65-84). 13 The poor neurocognitive function in school-aged HIVinfected children might be explained by many reasons.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The prevalence of speech-language impairments among children infected with HIV is relatively high [11]. Children infected with HIV who demonstrate language impairments would be at risk of poor academic performance [17]. Language impairment is classified as primary and concurrent; former being isolated language impairment without cognitive or hearing impairment and the latter language impairment being associated with cognitive and/or hearing impairment [18].…”
Section: Introductionmentioning
confidence: 99%